2018
DOI: 10.1371/journal.ppat.1007408
|View full text |Cite
|
Sign up to set email alerts
|

Multiple components of the nuclear pore complex interact with the amino-terminus of MX2 to facilitate HIV-1 restriction

Abstract: Human myxovirus resistance 2 (MX2/MXB) is an interferon-induced post-entry inhibitor of human immunodeficiency virus type-1 (HIV-1) infection. While the precise mechanism of viral inhibition remains unclear, MX2 is localized to the nuclear envelope, and blocks the nuclear import of viral cDNAs. The amino-terminus of MX2 (N-MX2) is essential for anti-viral function, and mutation of a triple arginine motif at residues 11 to 13 abrogates anti-HIV-1 activity. In this study, we sought to investigate the role of N-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(96 citation statements)
references
References 52 publications
7
89
0
Order By: Relevance
“…Antiviral functions of MX2 have been associated with its localization to the nuclear envelope; however, cytoplasmic localization has also been reported (Dicks et al, ; Melén et al, ). Cytoplasmic and nuclear fractionation of melanoma cell lines showed that MX2 protein is mainly found in the nuclear fraction, but a weak cytoplasmic localization was also detected (Figure g).…”
Section: Resultsmentioning
confidence: 99%
“…Antiviral functions of MX2 have been associated with its localization to the nuclear envelope; however, cytoplasmic localization has also been reported (Dicks et al, ; Melén et al, ). Cytoplasmic and nuclear fractionation of melanoma cell lines showed that MX2 protein is mainly found in the nuclear fraction, but a weak cytoplasmic localization was also detected (Figure g).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the association of MxB with nuclear pore structures (33)(34)(35)(36)(37) taken together with the demonstration of nuclear pore structures to be phase-separated condensates (51,52) points to the inference that MxB also associates with membraneless phase-separated condensates (see Figs.…”
Section: Discussionmentioning
confidence: 92%
“…Human MxA forms disparate membraneless structures solely in the cytoplasm and has antiviral activity towards several RNA-and DNA-containing viruses including orthomyxo-and rhabdoviruses (23)(24)(25)(26)(27)(28)(29), while human MxB is mainly associated with the cytoplasmic side of nuclear pores and additional cytoplasmic membraneless structures and the full-length MxB has antiviral activity against HIV and other lentiviruses by blocking entry of viral components into the nucleus (33)(34)(35)(36)(37). Murine Mx1 is mainly in nuclear bodies (it has a C-terminal nuclear localization signal), while murine Mx2 is mainly in cytoplasmic structures (23)(24)(25)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…This basic phenotype, moreover, is observed upon restriction of WT virus by the antiviral protein MxB (61). Although MxB is unlikely to be expressed at tangible levels under the conditions of viral infection used herein, recent reports have implicated components of the cellular nuclear import machinery in the mechanism of MxB antiviral activity (85,86). We accordingly propose that analysis of the effects of MA-CA coassembly on Nup153 and Nup358 binding to CA in vitro or in cells in the presence or absence of MxB may help to inform the molecular mechanism of altered MA-CA integration site targeting observed here.…”
Section: Discussionmentioning
confidence: 74%